PERAN MATA KULIAH PENDIDIKAN PANCASILA SEBAGAI MATA KULIAH WAJIB UMUM DALAM MENGEMBANGKAN KEPRIBADIAN MAHASISWA YANG SESUAI DENGAN NILAI-NILAI PANCASILA - Febrian Alwan Bahrudin (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2020)
This research was conducted to know the role of Pancasila education subject as general compulsory subject in developing students` personality based on Pancasila values. The background of this research was related to the problems which happened in this country: anarchism, radicalism, terrorism, and other problems those could be able to damage the unity and integrity of the republic of Indonesia. Therefore, Pancasila education subject must be implemented in a university, this is in accordance with Law No. 12 of 2012, article 35 paragraph 3. The place of this research was at Sultan Ageng Tirtayasa University. This research used qualitative approach and descriptive method. The results of this research shown that Pancasila education subject at Sultan Ageng Tirtayasa University had a very important role in developing students` personality in accordance with the values of Pancasila, this could be seen in learning achievements: cognitive, psychomotor, affective. In the achievement of cognitive, the students were taught some materials related to the semester learning plan, with the aim was to make students having knowledge of Pancasila, the achievement of psychomotor emphasized to students` skills by using learning methods as a form of student centered learning. In affective achievement could be seen in the students personality which had been in accordance with the values of Pancasila.